An Augmented Reality-Based Boardgame for Anti-Corruption Education: Design, Development, and Evaluation Using the MDLC Model - Naurah Qolbia Salamah; Irma Yuliana; Eko Prasetyo (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2026)
The objective of this study is to develop an Augmented Reality (AR)-based educational board game called SiKilat, which stands for “Ready to Fight Corruption and Nepotism,” to help students better understand anti-corruption principles. The Multimedia Development Life Cycle (MDLC) was employed, consisting of five stages: initialization, blueprint design, asset preparation, product development, and testing and validation. The focus of the study is university students. Interviews, expert reviews, and pre- and post-tests were used as data collection methods. The results indicate that the developed medium is effective and has the potential to enhance student engagement in learning. The Wilcoxon test yielded a significance value of 0.00018 (< 0.05), and the average score increased from 4.9 to 9.3. Consequently, the SiKilat AR board game helps students understand anti-corruption principles and can serve as an alternative interactive learning medium